2016
DOI: 10.1183/13993003.01180-2016
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1α: a key player for epithelial-to-mesenchymal signalling in COPD?

Abstract: @ERSpublicationsInterleukin-1 alpha released by airway epithelial cells may instruct fibroblasts to become proinflammatory in COPD http://ow.ly/CLYK301tyOjThe lungs are continuously exposed to inhaled particles and irritants. Tobacco smoking is the leading cause of several airway diseases, including lung cancer, idiopathic pulmonary fibrosis and chronic obstructive pulmonary disease (COPD). In COPD, repeated exposure to cigarette smoke induces chronic inflammation and structural remodelling of the airways, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…They further found that urokinase plasminogen activation receptor could be responsible for modulating EMT, positively correlating with an increase in vimentin expression in human small airways 40. Recent in vitro epithelial–fibroblast co-culture studies also examined the probable role of IL-1α in promoting EMT 41. They reported that IL-1α caused aberrant epithelial–fibroblast interactions when stimulated by CSE 42…”
Section: Introductionmentioning
confidence: 99%
“…They further found that urokinase plasminogen activation receptor could be responsible for modulating EMT, positively correlating with an increase in vimentin expression in human small airways 40. Recent in vitro epithelial–fibroblast co-culture studies also examined the probable role of IL-1α in promoting EMT 41. They reported that IL-1α caused aberrant epithelial–fibroblast interactions when stimulated by CSE 42…”
Section: Introductionmentioning
confidence: 99%